Photojournalism in Central Europe: on authenticity and ethics - Láb, Filip; Štefaniková, Sandra (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2016)
The development of the Internet and digital technology by the end of the twentieth century has raised serious disputes about ethics, authenticity and photo manipulation. These concerns are especially relevant in the field of photojournalism in the news media, where credibility matters the most. In this paper we described the current situation in relation to image authenticity and professional ethics in three countries of Central Europe – the Czech Republic, Poland and Slovakia. We asked research questions regarding photo production, circumstances of photographing, image content, technical improvements, manipulation, ethical standards and responsibility. Our findings reveal a complexity of ethical issues related to working with visual news material. During the fieldwork we conducted 65 in-depth interviews and surveys with full-time and freelance photojournalists and photo editors working for printed and online newspapers and opinion magazines in Central Europe.
Keywords: photojournalism; authenticity; ethics; manipulation